Pembentukan Karakter Birokrat Indonesia Yang Berakhlak, Birokrat, Karakter, Modernisasi, Teknologi - Dianni Risda; Encep Syarif Nurdin; Yadi Ruyadi (Jurnal Global Citizen : Jurnal Ilmiah Kajian Pendidikan Kewarganegaraan, 2023)
This study seeks to provide argumentative information regarding the reality of obstacles, challenges, strategies, and efforts in shaping the character of bureaucrats who have good morals, as well as to rationalize the importance of using technology, information, and communication in public services. This research was carried out through a qualitative approach with literature study methods, data analysis, namely, reduction, display, and verification or conclusion. The results of the research are: 1) dynamic and complex obstacles and challenges, leading to the reality of bureaucratic competence, mental distortion of serving , the Industrial Revolution 4.0, as well as legal certainty, 2) strategies and efforts in shaping the character of moral, capable bureaucrats through education and training, increasing technology literacy, supervision programs, and policies on welfare, 3) in the modern era, the bureaucracy needs to optimize technological progress , information and communication, to be effective and efficient, to be agile and professional. So that the formation of bureaucrats with character is an alternative solution in overcoming the stigma and stereotypes about the world of bureaucracy which is seen as rigid, conventional, procedural and pragmatic, so that it turns into world-class governance and public services.